2022
DOI: 10.18559/ebr.2022.4.2
|View full text |Cite
|
Sign up to set email alerts
|

World capital markets facing the first wave of COVID-19: Traditional event study versus sensitivity to new cases

Abstract: The aim of the paper is to analyse the impact of the new coronavirus on financial markets. The sample comprises returns from 80 countries, across all regions and incomes for the period known as the first wave. By combining event study methodology and time series analysis of new COVID-19 cases it is found that the negative price effect is widespread but unequal across regions. It is also noted that the distribution of the impact is also uneven with a high concentration in the week after the first local case but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The increased uncertainty resulting from the pandemic has prompted researchers to investigate the effects of COVID-19 on different asset returns, risk parameters, and the overall economy. Several studies found a negative impact of these shocks on financial markets, stocks performance, global economy, and level of risk (Anh & Gan, 2020;Angosto-Fernández & Ferrández-Serrano, 2022;Aslam et al, 2020;Goodell, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The increased uncertainty resulting from the pandemic has prompted researchers to investigate the effects of COVID-19 on different asset returns, risk parameters, and the overall economy. Several studies found a negative impact of these shocks on financial markets, stocks performance, global economy, and level of risk (Anh & Gan, 2020;Angosto-Fernández & Ferrández-Serrano, 2022;Aslam et al, 2020;Goodell, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%